2022
DOI: 10.21149/12710
|View full text |Cite
|
Sign up to set email alerts
|

Parental obesity and the transition from teenagers of normal-weight to young adults with obesity in Mexico

Abstract: Objective. To estimate to what extent the parental tran­sition to obesity affects the likelihood that normal-weight teenagers also transition to obesity. We depart from the hypothesis that the transition to obesity specifically among parents is the main factor affecting the development of obesity during adolescence. Materials and methods. Using two rounds of the longitudinal Mexican Family Life Survey (MxFLS) and logistic regressions, we investigated how family weight-related characteristics affected the likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Brambila et al [ 32 ] stated that the mechanism through which Mexican families may affect the weight of their children is an acceptance of a low level of physical activity and unhealthy eating patterns, including family meal times that have an important influence on overweight and obesity. Guerrero et al [ 33 ] reported that to reduce factors associated with obesity, it is essential to intervene in routine acquisition, which includes establishing eating schedules, exercising regularly, reducing sedentary lifestyles and establishing sleep routines.…”
Section: Discussionmentioning
confidence: 99%
“…Brambila et al [ 32 ] stated that the mechanism through which Mexican families may affect the weight of their children is an acceptance of a low level of physical activity and unhealthy eating patterns, including family meal times that have an important influence on overweight and obesity. Guerrero et al [ 33 ] reported that to reduce factors associated with obesity, it is essential to intervene in routine acquisition, which includes establishing eating schedules, exercising regularly, reducing sedentary lifestyles and establishing sleep routines.…”
Section: Discussionmentioning
confidence: 99%